The effects of electron beam and gamma ray irradiation levels in spray-dried animal plasma on nursery pig performance - C N Groesbeck; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
A total of 385 pigs (initially 13.4 ± 2.2 lb and 21 ± 3 d of age) were used in a 28-d trial to determine the effects of electron beam and gamma ray irradiation dosage of spray-dried animal plasma (plasma) on nursery pig performance. Pigs were allotted to pen and blocked by weight by using an incomplete block design with either 7 or 8 replications per treatment. Dietary treatments were randomly allotted to pen within block. Ten dietary treatments were fed from d 0 to 14, including: a negative control diet with no added plasma, a positive control diet with added plasma, or one of 8 irradiated plasma diets. The 8 irradiated treatments included plasma irradiated with either electron beam or gamma radiation at increasing dosages of 2, 4, 6, or 10 kGy. All the pigs were fed a common diet from d 14 to 28. Irradiation of the plasma reduced the total bacterial and coliform counts at every dose, regardless of irradiation source. There were no interactions (P>0.05) between irradiation source and dosage for the entire trial. From d 0 to 14, pigs fed the diets containing plasma had increased (P0.12) in growth performance between the pigs fed the plasma irradiated by electron beam or by gamma ray, which confirms previous research. But the majority of previous research has shown improvements in growth performance when pigs were fed diets with irradiated plasma, compared with performance of pigs fed diets containing regular plasma. Irradiation of plasma did not improve performance in this study.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Nursery pig; Spray-dried animal plasma; Irradiation; Swine